2015
DOI: 10.7439/ijbr.v6i5.1959
|View full text |Cite
|
Sign up to set email alerts
|

Inducible and constitutive clindamycin resistance in Staphylococcus aureus: an experience from Western Nepal

Abstract: Objective: This study aimed to determine prevalence of inducible and constitutive clindamycin resistance among clinical S. aureus isolates and also study their association with methicillin resistance. Methods: A cross-sectional study including 140 non-duplicate isolates of S. aureus was done. Isolates were identified by standard microbiological methods and methicillin resistance was detected by cefoxitin disc diffusion method. Inducible clindamycin resistance was detected by D-test. Results: Prevalence of indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 22 publications
4
16
5
Order By: Relevance
“…In this study the prevalence of i MLS B among S. aureus was found to be 11.48% which is similar to that reported by Ansari et al (12.4%) [24], Sah et al (12.1%) [14] from Nepal and Govindan et al (11.6%) from India [12]. Varying prevalence rates of i MLS B have been reported in different other studies; 18.2% from Nepal [25] 28.6% from Iran [11], 20.7% [13] and 24.3% [10] from India.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study the prevalence of i MLS B among S. aureus was found to be 11.48% which is similar to that reported by Ansari et al (12.4%) [24], Sah et al (12.1%) [14] from Nepal and Govindan et al (11.6%) from India [12]. Varying prevalence rates of i MLS B have been reported in different other studies; 18.2% from Nepal [25] 28.6% from Iran [11], 20.7% [13] and 24.3% [10] from India.…”
Section: Discussionsupporting
confidence: 88%
“…This study showed prevalence rate of 25.1% which is similar to the study done in eastern part of Nepal [21] India [2] and other part of the world [9]. However higher rates of MRSA were also noted in other studies conducted in Nepal [14, 2224] and other countries [10, 11, 13, 18]. These variations could be due to the differences in the circulating clones or due to the variations in infection prevention practices and trends of antibiotics prescription in different hospital set up.…”
Section: Discussionsupporting
confidence: 87%
“…(54.78%). [ 15 16 17 ] Lyall et al . had reported a very high percentage of MRSA (91.5%) in their study.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, cMLS B resistant phenotype was the most common and highest (40%) followed by MS B (37%) and iMLS B (23%) phenotypes. Varying prevalence rates of MLS B resistance phenotype are reported by other studies[15,17,27,28,29]. iMLS B was found higher (44%) in MRSA whereas it was cMLS B (36%) in MSSA.…”
mentioning
confidence: 64%